Pengaruh Abu Bonggol Jagung Sebagai Substitusi Semen Terhadap Kuat Tekan Beton Alir - Amalia, Taris Rizka; Rochmah, Nurul (Universitas Teuku Umar, 2024)
Abstract The use of flow concrete is the main choice in construction because of its high workability that facilitates compaction. In this study, utilizing corn cob ash as a partial substitution material for cement because the content of corn cob ash makes the waste potentially used as a concrete mixing material. One of the most important silica content in concrete is silica (SiO2). Corn cob ash has a fairly high silica content of 59%. Silica plays an important role in concrete because it can increase the compressive strength of concrete. This study aims to determine the effect of corn cob ash with variations of 0%, 4%, 5%, 7%, 9% on the compressive strength of flow concrete with a proportion of superplasticizer 1.5% at the age of 7, 21, and 28 days. From the results of the study, it can be concluded that the maximum compressive strength of concrete is in the CCA mixture of 7% at the age of 28 days of concrete, which is 35.22 MPa. The compressive strength of concrete with a mixture of 0% to 7% CCA continues to increase in each life of concrete. Based on the results of this study, corn cob ash as a partial substitution of cement can affect the compressive strength value of concrete. Keywords—Flow Concrete, Corn Cob Ash, Compressive Strength of Concrete